Model-based analysis of changes in the morphological characteristics of Moscow students for the last two decades - Negasheva, Marina Anatolevna (Array, 2020)
The aim of the paper is to develop a model of changes in morphological characteristics of young males and females body structure at the beginning of the 21st century. For this purpose the results of Moscow students’ annual screenings from 2000 to 2018 were analyzed (total number of 17–18-year-olds − 6,433 individuals). As a result, five factors describing the trends of changes were revealed and further analysis demonstrated variants of their values over time. An original model was developed, which reflected real morphological transformations in the body parameters of the young generation for the last 20 years. For both sex groups a trend towards macrosomia (gr. macros − big, soma- body) was revealed. For the boys some increase in linear traits was found with a decrease in muscularity. In girls, parabolic association between athletic characteristics and the year of investigation was found: the decrease in muscularity for the first decade, and its increase for the second one.